Study of Pathogenic Properties of Brucellosis Agents under Artificial Immunosuppression Conditions - B. A. Shabalin; V. Yu. Okhapkina; I. V. Darmov; S. L. Kuznetsov (Проблемы особо опасных инфекций, 2010)
The influence of artificial immunodeficiency state upon brucellosis course has been studied experimentally. Trials on laboratory animals demonstrated faster and more intensive progression of infectious process as well as increased frequency of the fatal cases of the disease caused by brucellosis agents.